Ukrainian poetry as a factor in national style formation in popular music genres - Artemenko, Violetta (Scientific herald of Tchaikovsky National Music Academy of Ukraine, 2025)
The relevance of the study. Current historical circumstances in Ukraine are heightening Ukrainians' curiosity about their own history and art. Using the example of individual songs of modern pop music publication examines to outline and specify poetic sources for musical creativity in mass genres modern Ukrainian pop-culture, as well as to clarify the possible influence of poetry on the dynamics of national style formation in the specified context. The main objective of the study is a Ukrainian poetry from various historical periods, including modern times, which inspires Ukrainian artists to be creative and actively artistically reflect on their own history and national musical style of speech in particular. The methodology includes the following methods: culturological (to characterize the basic features of the national style), structural-functional, genre, intonation-dramaturgical (for a holistic analysis of works), as well as the method of theoretical generalization (to summarize). The main results and conclusions. The high role of Ukrainian poetry as a strong stimulus for the manifestation and renewal of national features of musical creativity in formalized formats of the genre (style) is noted. Several groups of poetic sources are identified that serve as the basis for musical search. Several examples of the work of various performers are analyzed for the characteristic reproduction of features of the national poetic and musical style. The song “Gai Shumlyat” by the group “Pyrih i Batig” on the verses of P. Tychyna from the album “Poetic” (2016) is considered. The songs “Haltorna” by A. Pivovarov based on poems by L. Kostenko, “V nebi chistomu chuty grym” by Skofka, “Ne hody ti tut, ne hody” by Vivienne Mort based on poems by Maxim “Dali” Kryvtsov are analyzed. In addition, a number of songs by famous modern groups and performers are listed, demonstrating the active dynamics of the creative style in popular music precisely in the context of national principles. The following factors are determined as the main substantive and stylistic trends: the well-known influence of the poetic series itself on the musical series and as a result - the increase in declamation and role text, the strengthening of the dramatic element.. The second important feature in the style of creation is the direct influence of the poetic tradition on the emergence of such a genre as "incantation" in popular musical culture. At the same time, it is emphasized that a bright general feature of the national musical style of creation in pop culture is considered to be the active development of the national intonation fund, ranging from folk singing practices to folk poetic texts, musical texts, intonation thesaurus and folk instruments in general. And with all this, Ukrainian pop music clearly walks in the same vein with world trends in techno, or electronic music, or other stylistic branches